Optimal Medical Therapy for Chronic Coronary Syndrome: Realities and Prospects - P. A. Lebedev; I. K. Petrukhina; A. A. Garanin; E. V. Paranina (Рациональная фармакотерапия в кардиологии)
Combination therapy is the standard of treatment for virtually all current non-communicable diseases, primarily chronic coronary heart disease, in modern terminology - "chronic coronary syndrome" (CSS), arterial hypertension, chronic heart failure, diabetes mellitus. The need for a combination of drugs increases even more with comorbidity, which is a typical situation in clinical practice. The recently accumulated material requires a review of the possibility of percutaneous coronary intervention and coronary bypass surgery in prolonging the life of patients with CCS, focusing on providing optimal medical therapy (OMT) for each patient with CCS, based on long-term treatment with antiplatelet agents, statins, angiotensin converting enzyme in-hibitors/angiotensin receptor blockers, beta-blockers. OMT aimed at preventing cardiovascular events and relieving symptoms in patients with CCS requires maximum commitment - a key factor in achieving therapeutic goals. Insufficient adherence of patients to prescribed therapy and its absence are the main barriers to increasing the survival rate of patients with cardiovascular diseases in primary and secondary prevention in the Russian Federation, as evidenced by numerous registers. The desire of the doctor to individualize treatment, which inevitably complicates the use of drugs, pushes patient adherence to treatment into the background. As a result, the patient's lack of commitment to each of the pharmaceuticals destroys the applicability of the OMT concept. A great achievement of the current stage of development of clinical cardiology and the pharmaceutical industry is the ability to offer patients optimal single pill combinations (SPC) in terms of effectiveness, tolerability, drug interactions, and ease of use. The article substantiates the prospects for a successful solution of this key problem by using a new generation of SPC components belonging to different pharmacological groups. The combination of three components (lisinopril, amlodipine and rosuvastatin), each of which has pleiotropic effects, provides a multi-targeted effect with a single dose, with the possibility of individualization of therapy, which is provided by four dosage options within this SPC.